RELATION OF COVERT VISCERAL ADIPOSITY AND SUBCLINICAL ATHEROSCLEROSIS PRESENTATION IN TYPE 2 DIABETES MALE PATIENTS - A. Е. Filippov; A. A. Sergoventsev; B. V. Pomogaibo (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the prevalence of covert visceral adiposity (CVA) in males with type 2 diabetes (DM2) and to assess its relation with subclinical atherosclerosis and food-related behavior.Material and methods. To the study, 72 middle age males included (54,1±0,7 y.o.). Mean duration of DM25,1±1,1 years. In 28 patients DM2 had been diagnosed first time in the study. Those with body mass index (BMI) >30 kg/m2 and waist circumference >102 cm were excluded. All patients underwent standard clinical investigations and additionally, leptin levels measurement in blood serum, with bioelectrical impedance measurement of adipous tissue amount, duplex scan of carotid and femoral arteries; the EAT-26 questionnaire was applied.Results. In the group of participants, CVA prevalence was 31%. In this group of patients there were significantly higher BMI, waist circumference low density lipoproteides levels and leptin. At atherosclerosis assessment in carotid and femoral arteries, CVA associated with more significant and multifocal lesion. In regression analysis, the sum of plaques number correlated with the age, BMI, systolic blood pressure, low density lipoproteides levels.Conclusion. CVA might have significance in the increase of cardiovascular risk in middle aged males with normal BMI and with no obesity.